Analysis of the Utilization of Nature as a Learning Media in the Covid-19 Pandemic Era - Fatmawati, Fatmawati; Yusrizal, Yusrizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Nature is a very effective learning resource in learning in the pandemic era, the use of nature or the environment is the main capital for teachers to create interesting learning. Different natural conditions and situations provide an interesting experience for elementary school students to add new knowledge in the pandemic era. The purpose of this study was to determine the benefits of nature as a learning medium in the pandemic era. This type of research is descriptive analysis with a qualitative approach. Data collection techniques used are observation, interviews and documentation. The results showed that. 1) nature is the best medium during a pandemic; 2) the use of Nature as a learning medium provides a new nuance for the student learning process; 3) good use of nature for the learning process has a positive impact on interest, motivation and student learning outcomes.